2020
DOI: 10.1371/journal.pone.0237232
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for contamination as the origin for bacteria found in human placenta rather than a microbiota

Abstract: Until recently the in utero environment of pregnant women was considered sterile. Recent high-sensitivity molecular techniques and high-throughput sequencing lead to some evidence for a low-biomass microbiome associated with the healthy placenta. Other studies failed to reveal evidence for a consistent presence of bacteria using either culture or molecular based techniques. Comparing conflicting "placental microbiome" studies is complicated by the use of varied and inconsistent protocols. Given this situation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 44 publications
7
33
0
Order By: Relevance
“…Despite numerous papers published on this field, the concerns of contamination remain unsolved. In the newest study investigating this issue, evidences were put forward for contamination as the origin of bacteria found in human placenta samples (Gschwind et al, 2020).…”
Section: First Microbial Colonizationmentioning
confidence: 99%
“…Despite numerous papers published on this field, the concerns of contamination remain unsolved. In the newest study investigating this issue, evidences were put forward for contamination as the origin of bacteria found in human placenta samples (Gschwind et al, 2020).…”
Section: First Microbial Colonizationmentioning
confidence: 99%
“…It is important to highlight that sampling methods have also been assessed by some authors; for example, a study including placenta samples from 20 term and preterm deliveries found bacterial DNA in the samples, but after analyzing the sequences, the differences with the negative controls were not significant [14]. In another study, bacteria were found in fetal membranes and umbilical cords but never inside the placenta, supporting the hypothesis of contamination as the source of bacterial presence in studies that challenge the "sterile womb" hypothesis [15]. As for the amniotic fluid, a recent study in a bovine C-section model revealed some positives (5 out of 24), with low amounts of bacteria in the meconium, but none of the amniotic fluid samples presented different amounts of bacterial DNA compared to the negative controls [16].…”
Section: Introductionmentioning
confidence: 95%
“…Recent high-quality studies have questioned the presence of a distinct placental microbiome 15 20 and an amniotic fluid microbiome 21 , 22 . Yet, in animal models, maternal bacteria have been suggested to actively colonize the fetal gut before birth 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%